Kajian Simbolisme Budaya Clifford Geertz Terhadap Tradisi Larangan Memakan Ikan Lele di Kecamatan Glagah Kabupaten Lamongan - Moch Rifki Firdaus (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2025)
The prohibition against consuming catfish in Glagah District, Lamongan Regency, is a local tradition that persists amid modernization and globalization. This tradition functions not merely as a dietary restriction but as a cultural symbol rich in historical, spiritual, and social meaning, reflecting the community’s collective identity and worldview. This article aims to examine the tradition through Clifford Geertz’s cultural symbolism approach, which views culture as a system of meaning woven by humans and expressed through symbols. The study is empirical in nature and employs qualitative methods. Primary data were collected through in-depth interviews with the caretaker of Boyopatih’s tomb, descendants of the tradition bearers, and younger community members, supported by secondary data from relevant literature. The findings reveal that the catfish taboo operates as a collective symbol reproduced through mythic narratives, cultural practices, and intergenerational oral transmission. Although the meaning of the symbol is shifting among younger generations, it continues to function as a tool of social control and a marker of cultural identity. This study contributes to a deeper understanding of how local symbols sustain traditional values and opens opportunities for further research on symbolic adaptation in times of social change. Keywords: cultural symbolism, Clifford Geertz, local tradition, catfish taboo.